2008
DOI: 10.21273/hortsci.43.5.1423
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Management with Cover Crops and Compost Affects Development and Yield in Organically Managed Sweetpotato Systems

Abstract: A 3-year field experiment was initiated in 2001 to evaluate different organic sweetpotato production systems that varied in cover crop management and tillage. Three organic systems: 1) compost and no cover crop with tillage (Org-NCC); 2) compost and a cover crop mixture of hairy vetch and rye incorporated before transplanting (Org-CCI); and 3) compost and the same cover crop mixture with reduced tillage (Org-RT) were compared with a conventionally managed system (Conv) with tillage and chemical control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…polyphenol and mineral content). We also assumed no significant differences in yield, as studies on other crops found that transition from intensive conventional cropping system to low‐input cropping system does not involve differences in terms of final yield . Currently the artichoke in the Mediterranean basin, of which Sardinia is a fully representative area, is grown according to traditional methods relying on monoculture systems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…polyphenol and mineral content). We also assumed no significant differences in yield, as studies on other crops found that transition from intensive conventional cropping system to low‐input cropping system does not involve differences in terms of final yield . Currently the artichoke in the Mediterranean basin, of which Sardinia is a fully representative area, is grown according to traditional methods relying on monoculture systems .…”
Section: Introductionmentioning
confidence: 99%
“…We also assumed no significant differences in yield, as studies on other crops found that transition from intensive conventional cropping system to low-input cropping system does not involve differences in terms of final yield. [15][16][17][18] Currently the artichoke in the Mediterranean basin, of which Sardinia is a fully representative area, is grown according to traditional methods relying on monoculture systems. 19 The autumn-winter production is normally destined for fresh consumption, while that harvested during the spring period is used by the processing industry.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of rolling a rye + vetch mixture was compared to conventional tillage prior to applying PL on a subsequent sweetpotato crop in Florida in 2001, 2002, and 2004 (Treadwell, Creamer, Hoyt, & Schultheis, 2008). Yields tended to be lower in the rolled plots.…”
Section: Dual‐use Cover/green Manure Cropsmentioning
confidence: 99%
“…Aboveground DM production of species or mixtures was variable in many CGM studies in the southeastern United States (Parr et al., 2011; Reberg‐Horton et al., 2012; Treadwell et al., 2007, 2008; Vann et al., 2017). Endemic fluctuations in weather variables help explain this variation.…”
Section: Dual‐use Cover/green Manure Cropsmentioning
confidence: 99%
“…Several studies have shown that organic production is comparable to conventional systems in terms of yield; however, organic systems had enhanced microbial biomass and activity, increased soil organic matter, increased nutrient pools, and other soil properties (Delate et al, 2003;Klonsky, 2000). A study comparing compost with or without cover crops and tillage on organic vs. conventional sweetpotato production showed that leaf N, P, and K concentrations were greatest in the compost/ cover crop combination compared with the other systems (Treadwell et al, 2008). Other studies found greater P, Mg, and Fe levels in organic systems and those mineral nutrients were on average higher in organically grown crops though results were somewhat inconclusive (Worthington, 2001).…”
mentioning
confidence: 99%